Effectiveness of Guided Imagery to %FEV1, Absolut Neutrophil, Anxiety, and Quality of Life in Stable Chronic Obstructive Pulmonary Disease (COPD) Patient - Herlina, Liana; Sutanto, Yusup Subagio; Nugroho, I.G.B Indro; Harsini, Harsini; Prasetya, Windu (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2024)
Background: Chronic obstructive pulmonary disease (COPD) is a leading factor in morbidity and mortality worldwide associated with excessive chronic inflammatory response. Guided imagery is a relaxation technique to achieve the desired positive outcome. This study analyzed the effectiveness of guided imagery in stable COPD patients on the value of % FEV1, absolute neutrophils, anxiety, and the standard of living in those with steady COPD.Methods: Experimental analytic research with quasi-experimental, pretest and post-test design. Subjects were outpatient stable COPD patients at the pulmonary polyclinic of UNS Surakarta Hospital in January-June 2022. Subjects were divided into guided imagery intervention groups for 4 weeks and controls. Subjects were then examined for %FEV1 by spirometry, absolute neutrophils, Taylor Minnesota Anxiety Scale (TMAS) questionnaire, and St. George Respiratory Questionnaire (SGRQ) quality of life questionnaire, and re-evaluated after four weeks.Results: There were 32 research subjects. The findings demonstrated that the therapy group did not endure a significant increase in the mean value of %FEV1 (P=0.617). Meanwhile, the mean value of %FEV1 significantly decreased in the control group (P=0.025), given that the control group's value of % FEV1 fell. In contrast, the treatment group's increased, even if the difference was not statistically significant, the use of guided imagery could effectively halt the decline in %FEV1 value. Compared to the control group (P=0.014), the TMAS anxiety score was lower in the treatment group (P≤0.001). The overall SGRQ score (quality of life) considerably decreased in the treatment group (P≤0.001) while significantly increasing in the control group (P=0.014). Absolute neutrophils were found in both the treatment group and the control group (P=0.642; P=0.224, respectively). Absolute neutrophil blood levels in the treatment and control groups did not differ significantly.Conclusion: Guided imagery is effective on %FEV1 values, anxiety, and quality of life in stable COPD patients but not against absolute neutrophils.